1954
DOI: 10.1677/joe.0.0100111
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Steroid Hormones on the Energy Metabolism of the Adrenal Cortex in Vitro

Abstract: The action of different steroid hormones on the oxygen consumption of adrenal cortex slices in vitro was investigated.Deoxycorticosterone (DOC), testosterone and dehydroisoandrosterone, and 17-hydroxycorticosterone, were found to stimulate the oxygen uptake rate, while cortisone, progesterone, pregnenolone, androsterone and cholesterol were inactive. Pretreatment of the slices with DOC, testosterone or ACTH inhibited the action of ACTH or DOC added subsequently. The significance of the direct action of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1955
1955
1971
1971

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Since the response to oestrogen is so different from the changes initiated by ACTH it seems unlikely that the Latter is responsible for the increased DHA output. One may, however, consider the possibility of a direct action on the adrenal cortex by the oestrogen, particularly as certain steroids have been shown to have a direct stimulatory influence on adrenocortical metabohsm [Brummel, Halkerston & Reiss, 1954]. Lieberman & Teich [1953] have suggested that DHA might arise from 5:3ß: 17-diol C21 metabolites derived from intermediates in the biogenesis of the corticosteroids by hydroxylation at C17 prior to conversion of the A5:3/?…”
Section: Resultsmentioning
confidence: 99%
“…Since the response to oestrogen is so different from the changes initiated by ACTH it seems unlikely that the Latter is responsible for the increased DHA output. One may, however, consider the possibility of a direct action on the adrenal cortex by the oestrogen, particularly as certain steroids have been shown to have a direct stimulatory influence on adrenocortical metabohsm [Brummel, Halkerston & Reiss, 1954]. Lieberman & Teich [1953] have suggested that DHA might arise from 5:3ß: 17-diol C21 metabolites derived from intermediates in the biogenesis of the corticosteroids by hydroxylation at C17 prior to conversion of the A5:3/?…”
Section: Resultsmentioning
confidence: 99%